2010
DOI: 10.1123/jsm.24.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Employee Satisfaction in Sport: Development of a Multi-Dimensional Model in Coaching

Abstract: Despite the overwhelming emphasis on job satisfaction in sport management research, scholars continue to advocate for the distinctiveness and importance of evaluating both job satisfaction and dissatisfaction. The purpose of this investigation is to develop a model of job satisfaction and dissatisfaction for intercollegiate coaches. Fifteen head coaches participated in semistructured interviews. Results revealed a sport industry speci c three-factor model. Desirable job factors (Player-Coach Relationships, Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
(57 reference statements)
4
32
1
2
Order By: Relevance
“…These studies indicated that factors such as time in the season (Kelley, 1994), gender of the coaches (Kelley et al, 1999), years of experience (Kelley & Gill, 1993), and trait anxiety (Vealey, Udry, Zimmerman, & Soliday, 1992) influenced coaches' perceptions of stress and coach burnout. Additional understanding of this area can be gained from research examining coaches' job satisfaction and factors influencing coach retention (e.g., Allen & Shaw, 2009;Dixon & Warner, 2009;Inglis, Danylchuk, & Pastore, 1996). This research has highlighted that factors such as organisational support, flexibility and control, quality of supervision, salary, relations with others, and recognition of coaches' contributions might influence the satisfaction coaches have with their position and their intentions to remain in the role.…”
Section: Personal and Situational Factors Influencing Coaches' Percepmentioning
confidence: 99%
“…These studies indicated that factors such as time in the season (Kelley, 1994), gender of the coaches (Kelley et al, 1999), years of experience (Kelley & Gill, 1993), and trait anxiety (Vealey, Udry, Zimmerman, & Soliday, 1992) influenced coaches' perceptions of stress and coach burnout. Additional understanding of this area can be gained from research examining coaches' job satisfaction and factors influencing coach retention (e.g., Allen & Shaw, 2009;Dixon & Warner, 2009;Inglis, Danylchuk, & Pastore, 1996). This research has highlighted that factors such as organisational support, flexibility and control, quality of supervision, salary, relations with others, and recognition of coaches' contributions might influence the satisfaction coaches have with their position and their intentions to remain in the role.…”
Section: Personal and Situational Factors Influencing Coaches' Percepmentioning
confidence: 99%
“…são necessárias mais investigações que esclareçam melhor esta dimensão da liderança. (36) . além disso, a preocupação com aspectos como a explicação dos objetivos e do processo do treino e o estabelecimento de uma relação próxima com os atletas, envolvendo-os, dando-lhes responsabilidades, convencendo-os, seduzindo-os acerca das metas propostas, e criando um ambiente de treino que fomentasse o seu entusiasmo e a motivação, são consonantes com resultados de diversos estudos (e.g., 7,31,42,57) .…”
Section: Gestão De Conflitosunclassified
“…no entanto, também se verificou uma certa alternância nas decisões assumidas, pois muitos treinadores podiam, por vezes, tomar decisões de forma autocrática, ou, em algumas ocasiões, não interferir nas ações dos atletas durante o treino. além disso, como sugerido por dixon e Warner (36) , não deixavam de partilhar responsabilidades com os seus jogadores e de manter uma relação próxima com os mesmos, dando-lhes liberdade de escolha e até suporte social, e aproximando-se da intenção de criar um ambiente de apoio (42) . esta variação vai ao encontro das afirmações de buceta (19) , que sugere que os profissionais do treino devem possuir o conhecimento e a habilidade para utilizarem todos os estilos em função dos envolvidos e das circunstâncias.…”
Section: -Rpcd 11 (3)unclassified
“…In other words, what motivates a person to continue practising an activity (in this case, work) is the person's engagement in an activity that (a) they feel they are good at (competence), (b) allows them to develop personal initiatives (autonomy), and (c) connects them to others within a social environment (relatedness). Given that the conceptualisation of passion has been derived from SDT -and its central premise -it is expected that employee's passion will have an influence on job satisfaction, which has been defined as the degree to which employees are generally happy with their work (Hackman and Oldham, 1975), Mainly within the context of intercollegiate coaches, job satisfaction has been the subject of examination within the sport management context in relation to turnover, performance or leadership (e.g., Chelladurai and Ogasawara, 2003;Dixon and Warner, 2010;Li, 1993;Snyder, 1990). However, only three notable studies (none of them from the sport working context) have examined the relationship between passion and job satisfaction, with results largely showing that harmonious passion may be positive for job satisfaction and obsessive passion negative (Carbonneau et al, 2008;Thorgren et al, 2013;Vallerand et al, 2010).…”
Section: Job Satisfaction and Career Satisfaction As Outcomes Of Passionmentioning
confidence: 99%